Role of colonoscopy in the diagnosis and treatment of pediatric lower gastrointestinal disorders - Jae Hong Park (Korean Pediatric Society, 2010)
The safety and effectiveness of colonoscopy in the investigation of lower gastrointestinal tract pathology in children has been established for more than 2 decades in Korea. Skill and experience have since advanced to the point that both diagnostic and therapeutic colonoscopy are now routinely performed by most pediatric gastroenterologists. Pediatric colonoscopy differs significantly from its adult parallels in nearly every aspect including patient and parent management and preparation, selection criteria for sedation and general anesthetic, bowel preparation, expected diagnoses, instrument selection, imperative for terminal ileal intubation, and requirement for biopsies from macroscopically normal mucosa. Investigation of inflammatory bowel disease, whether for diagnosis or follow-up evaluation, and suspected colonic polyps are the most common indication for pediatric colonoscopy. The child who presents with signs and symptoms of lower gastrointestinal disorder should undergo colonoscopy with biopsy to make the diagnosis, as well as to help determine the appropriate therapy. This review introduces practical information on pediatric colonoscopy, the author's experiences, and the role of colonoscopic examination in the diagnosis and treatment of pediatric lower gastrointestinal disorders.